Auctions versus Posted Prices in Online Markets - Einav, Liran; Farronato, Chiara; Levin, Jonathan; Sundaresan, Neel (Journal of Political Economy, 2018)
Auctions were very popular in the early days of internet commerce, but today online sellers mostly use posted prices. We model the choice between auctions and posted prices as a trade-off between competitive price discovery and convenience. Evidence from eBay fits the theory. We then show that the decline in auctions was not driven by compositional shifts in seller experience or items sold, but by changing seller incentives. We estimate the demand facing sellers and document falling sale probabilities and falling relative demand for auctions. Both favor posted prices; our estimates suggest the latter is more important for the auction decline. Survey evidence provides further support.